Obstructive sleep apnea therapy for cardiovascular risk reduction—Time for a rethink?. Issue 12 (17th November 2021) - Dissanayake, Hasthi U.; Colpani, Juliana T.; Sutherland, Kate; Loke, Weiqiang; Mohammadieh, Anna; Ou, Yi‐Hui; de Chazal, Philip; Cistulli, Peter A.; Lee, Chi‐Hang
Abstract: Obstructive sleep apnea (OSA) is a highly prevalent and underdiagnosed medical condition, which is associated with various cardiovascular and metabolic diseases. The current mainstay of therapy is continuous positive airway pressure (CPAP); however, CPAP is known to be poorly accepted and tolerated by patients. In randomized controlled trials evaluating CPAP in cardiovascular outcomes, the average usage was less than 3.5 hours, which is below the 4 hours per night recommended to achieve a clinical benefit. This low adherence may have resulted in poor effectiveness and failure to show cardiovascular risk reduction. The mandibular advancement device (MAD) is an intraoral device designed to advance the mandible during sleep. It functions primarily through alteration of the jaw and/or tongue position, which results in improved upper airway patency and reduced upper airway collapsibility. The MAD is an approved alternative therapy that has been consistently shown to be the preferred option by patients who are affected by OSA. Although the MAD is less efficacious than CPAP in abolishing apnea and hypopnea events in some patients, its greater usage results in comparable improvements in quality‐of‐life and cardiovascular measures, including blood pressure reduction. This review summarizes the impact of OSA on cardiovascular health, the limitations of CPAP, and the potential of OSA treatment using MADs in cardiovascular risk reduction.